ENSINO DE LIBRAS COMO L2M2 EM AVAs: UMA ANÁLISE DO CURSO LIVRE DA UEMANET À LUZ DA COMPLEXIDADE - ALENCAR, Waldérick de Oliveira Mendes (2025)
This research deals with Brazilian Sign Language (BSL) teaching as a Second Language of the Second Modality in Virtual Learning Environments (VLE), focusing on the free basic course of BSL offered by UEMAnet, it uses the Complexity Theory with emphasis on the characteristics of Complex Adaptive Systems (CAS). This study has the general objective of analyzing the marks of complexity of BSL teaching as a Second Language of the Second Modality in this educational environment, considering BSL teaching as much as VLE of UEMAnet as a Complex Adaptive System. Based on Complexity Theory of Edgar Morin (2015) and authors such as Larsen-Freeman (1997), Paiva (2014), Borges e Silva (2016), Souza (2011), and others, the research explores the challenges of teaching a kinesiological-visual language as a BSL in virtual environments. Methodologically, qualitative analyses of the course contents were analyzed, with emphasis on the structure, technological resources and pedagogical practices adopted for the formation of BSL listeners as a Second Language of the Second Modality in distance mode. With emphasis on self-organization and adaptability of CAS, the analysis shows that the VLE allows flexible and autonomous learning, this is essential for the introduction of basic signs and grammar structures of the BSL as a Second Language. This work highlights the importance of VLE in democratizing access to education in BSL as a Second Language of the Second Modality. Also addressing the sociocultural implications and the contribution of the distance learning modality to the use, dissemination and enhancement of Sign Language. However, the research also identifies specific limitations such as lack of synchronous interactions and immediate feedback that are fundamental to fluency in a kinesic-visual language. The absence of gamified environments and collaborative spaces impairs interactive practice, hindering the integral development of students’ language skills. Finally, technological and methodological improvements are suggested as the insertion of collaborative tools to expand the potential of BSL teaching as a Second Language of the Second Modality in VLE, promoting a more dynamic and interactive educational experience.